An analysis of binary microlensing event OGLE-2015-BLG-0060 - Tsapras Y; Cassan A; Ranc C; Bachelet E; Street R; Udalski A; Hundertmark M; Bozza V; Beaulieu JP; Marquette JB; Euteneuer E; Bramich DM; et al. (Oxford University Press on behalf of the Royal Astronomical Society, 2019)
We present the analysis of stellar binary microlensing event OGLE-2015-BLG-0060 based on observations obtained from 13 different telescopes. Intensive coverage of the anomalous parts of the light curve was achieved by automated follow-up observations from the robotic telescopes of the Las Cumbres Observatory. We show that, for the first time, all main features of an anomalous microlensing event are well covered by follow-up data, allowing us to estimate the physical parameters of the lens. The strong detection of second-order effects in the event light curve necessitates the inclusion of longer-baseline survey data in order to constrain the parallax vector. We find that the event was most likely caused by a stellar binary-lens with masses M = 0.87 pm 0.12 mathrm{M} and M = 0.77 pm 0.11 mathrm{M}. The distance to the lensing system is 6.41 ± 0.14 kpc and the projected separation between the two components is 13.85 ± 0.16 au. Alternative interpretations are also considered.
Keywords: gravitational lensing: micro; methods: observational; techniques: photometric; Galaxy: bulge